Study on Flexural Performance of Integral Ceramic Wool-AAC Composite Wall Panel - Wang, Diqing (Scientific Journal of Technology, 2026)
To study the flexural performance of ceramic wool autoclaved aerated concrete composite wall panels (ceramic wool-AAC composite wall panels for short), four-point bending tests were conducted on the composite wall panels. The failure load of the panels was the measured value corresponding to the failure criteria specified in the code. The influences of structural forms on the flexural capacity, deflection, mid-span strain, interlayer slip and failure phenomena of the wall panels were discussed. The research results provide a theoretical basis and experimental data support for the design and application of ceramic wool-AAC composite wall panels.